The market for retirement products in Sweden - Palmer, Edward E., 1945- 1945- (Policy research working paper, 2008)
"Far-reaching changes in the regulation of financial markets and the organization of public pensions in the 1980s and 1990s transformed the landscape for retirement products in Sweden. First, banking and insurance were extensively deregulated in the 1980s, while the securities markets experienced major expansion. Insurance received a large boost from the authorization of unit-linked products in the early 1990s. Second, the public pension system was reformed. Survivor benefits for widows were eliminated from the public pillar in the late 1980s, leading to a large increase in demand for term life insurance. The old defined benefit public pension system was replaced by a notional or nonfinancial defined contribution (NDC) scheme, while a funded defined contribution (FDC) component was also created in the public pillar. The four occupational pension funds that cover the majority of Swedish workers were also converted into FDC schemes. This paper reviews the implications of these changes for the Swedish annuity market. It discusses the regulation of payout options in Sweden, highlighting the compulsory use of life annuities in the public pillar and the preference for term annuities in the occupational funds. It examines the performance of providers of retirement products, including the PPM, and reviews the increasing focus on risk-based regulation and supervision. The paper also emphasizes Sweden's success in moving in the direction of increased funding and privatization of old age insurance, while maintaining its basic character as a highly developed welfare state. "--World Bank web site